Pharmacokinetics of (-)-folinic acid after oral and intravenous administration of the racemate. - Greiner, P O (1989)
1. A pharmacokinetic study of the natural (-)-isomer of folinic acid ((-)-5 CHOTHF) and of total (-)-folates was performed in 12 healthy subjects after i.v. and oral administration of the racemic form of folinic acid. 2. After a 25 mg i.v. injection, (-)-5 CHOTHF kinetics were described by a biexponential function. The mean steady state volume of distribution (Vss) was 161; systemic and renal clearances averaged 335 and 53 ml min-1, respectively. After the same oral dose, (-)-5 CHOTHF was rapidly absorbed. Plasma concentrations of unchanged drug were much lower than those achieved after i.v. administration but in nine subjects, the disposition kinetics were also biexponential. Absolute bioavailability was only 4% as a consequence of a significant intestinal first pass effect. 3. AUC and t1/2Z values for total (-)-folates were similar after both routes of administration, indicating that the drug was fully absorbed. However the AUC of the active metabolite after i.v. dosage was only half that after oral dosage. 4. The amounts of total (-)-folates excreted in urine after both routes of administration were not significantly different and averaged one third of the dose after 24 h, whereas excretion of (-)-5 CHOTHF was three times less after oral treatment than after parenteral treatment. 5. Oral administration is a more suitable route for folinic acid therapy because more of the active metabolite is produced than after parenteral injection.